THE INFLUENCE OF CSR DISCLOSURE ON DEBT MATURITY STRUCTURE: EVIDENCE FROM INDONESIAN NON-FINANCIAL FIRMS - Ahmad Hakim; Dwi Nastiti Danarsari (Berkala Akuntansi dan Keuangan Indonesia, 2026)
Corporate Social Responsibility (CSR) disclosure has become an essential element of modern corporate sustainability practices. Prior research, however, presents conflicting evidence regarding its influence on a firm's debt maturity structure. Some studies argue that CSR disclosure enhances reputation and transparency, strengthening creditor trust and enabling firms to secure more long-term financing. Conversely, other findings suggest that CSR disclosure may lead to overinvestment and unfavorable signaling, potentially prompting firms to rely more on short-term debt. Addressing this gap, this study examines how CSR disclosure influences debt maturity structure in non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. CSR disclosure is measured using a Global Reporting Initiative (GRI) based index, while debt maturity structure is assessed through the long-term debt to total debt ratio. Using purposive sampling, panel data analysis is conducted through the fixed effect model (FEM) and the panel estimated generalized least squares (EGLS) estimator with cross-section weights, complemented with diagnostic tests. The findings reveal a significant positive relationship between CSR disclosure and debt maturity structure, supporting the view that CSR disclosure enhances credibility and information quality. Additional control variables like leverage, business risk, asset maturity, and interest rate term structure, also significantly influence debt maturity structure decisions. This study contributes to managerial and regulatory insights by demonstrating how CSR disclosure can function as a strategic financing tool to strengthen both sustainability and financial stability.